Cardiopericardial wounds in hospitals medium complexity: Our experience - Nitto, Daniel Alberto; Bregman, Abraham; Verger, Alejandro; Prado, Fabián (Cirugía del Uruguay, 1994)
Eight operated patients are shown, undergoing open cardiopericardial wounds. Those operations were performed in the Emergency and Surgery Service al Municipal Moran Hospital during 1980 and 1990. Preoperative status type os wound, associated lesions surgical tactique and technique ald morbimortality, were considered further considerations were made on history of cardiopericardial on open trhauma surgery.